ANTIBIOTIC GROWTH PROMOTERS (CINNAMOMUM CEYLON, ZINGIGBER OFFICINALE AND MORINGA OLEIFERA) AS PHYTOGENIC FEED ADDITIVES IN BROILER PRODUCTION: EFFECTS ON HEMATOLOGY, ANTIOXIDANT STATUS, INTESTINAL MICROBIOTA, CARCASS ANALYSIS AND SENSORY EVALUATION. - Daramola , Olajumoke Temidayo; Acheneje , Patrick (International Journal of Allied Sciences (IJAS), 2025)
An eight-week feeding trial was conducted to evaluate the effect of 0.2% Cinnamon powder, 0.2% ginger root powder, and 0.2% Moringa oleifera leaf meal on the hematological, antioxidant activities in serum, intestinal microbiota, carcass analysis, internal organs, and sensory evaluation of broiler chickens. One hundred and twelve broiler chicks were randomly allocated to four experimental diets replicated four times (28birds per diet; 7 birds per replicate) using a Completely Randomized Design. A basal diet was divided into four portions designated diet 1 (control) and diets 2, 3, and 4 supplemented with 0.2% cinnamon powder, 0.2% ginger root powder, and 0.2% Moringa oleifera leaf meal, respectively. At the end of the 56th day, four birds were randomly selected from each treatment for the determination of the aforementioned parameters. The results showed that packed cell volume (PCV), red blood cell (RBC) and hemoglobin (Hb) were significantly (P<0.05) influenced by the treatments. The phytogenic feed additive supplementation increased (P<0.05) the levels of catalase and glutathione peroxidase in broilers compared to the birds on control diet. The intestinal microbiota of broiler chickens was not influenced (P>0.05) by phytogenic feed additives supplementation. The 0.2% Moringa oleifera leaf meal supplementation enhanced broilers’ carcass characteristics. There was significantly (P<0.05) decrease in the texture and juiciness of breast meat of broilers fed diet 2 at 7.45 and 7.25, respectively. The color and flavor of breast meat of broilers fed diet 3 were significantly (P<0.05) decreased. It was concluded that the inclusion of 0.2% Moringa oleifera leaf meal in the diet of broiler chickens has beneficial effects.